THE ROLES OF JAWATANKUASA KESELAMATAN DAN KEMAJUAN KAMPUNG (JKKK) AS CHANGE AGENT: ISSUES AND CHALLENGES OF POLICY IMPLEMENTATION IN THE RURAL AREAS - Sharon Pearl Henry Serub; Noni Harianti Junaidi (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
In development administration, the public policies are purposely introduced by the government as a change sponsor towards a specific target group in society to encourage positive change. To ensure that these policies are implemented properly, it is the responsibility of policy implementers who take on the roles of change agents to bring changes into society. Generally, these change agents are the civil servants who have been trained specifically for these roles to ensure that the policies planned and introduced will be able to achieve their intended goals. As a developing country, the policies introduced by the government are majority development policies for both the urban and rural areas. For this purpose, the government set up specific ministry for the sole purpose of developing the rural areas in the country to narrow the gap between both areas. As such the change agents responsible for implementing the various programs under the rural development policies need to ensure that the rural population, namely the target groups, are ready and prepared to accept these changes. This is where the important roles of the JKKK comes in as the secondary change agents to provide support for the civil servants in undertaking the tasks of policy implementation. This paper seeks to identify the general issues and challenges faced by the JKKK as secondary changes in assisting the government to ensure that the implementation of public policies can proceed without much hassles as to ensure the policy goals are achieved. The understanding from such endeavours will encourage better preparation and communication between the government (change sponsor), the civil servants (primary change agent) and the target groups in the rural areas.